Giant hot electron thermalization via stacking of graphene layers. (25th January 2023) - Du, Sichao; Xie, Hao; Yin, Juxin; Sun, Yunlei; Wang, Qiuting; Liu, Hong; Qi, Wei; Cai, Chunfeng; Bi, Gang; Xiao, Duo; Chen, Wenchao; Shen, Xiaoyan; et al.
Abstract: The capability of graphene to generate hot electrons is predicted to be effective in converting low energy photons into electrical currents for the mid-infrared photodetection [1, 2]. However, the quantum yield of such hot electrons is not sufficient due to the limited thickness of two-dimensional graphene [3-5]. Therefore, it raises the question whether the electron thermalization is efficient enough to generate a large number of hot electrons in graphitic materials as a detectable photocurrent. Here, an experimental demonstration of the sufficient hot electron generation in Bernal stacking sequence nano-graphite films is presented. A comprehensive layer number dependence (1–120-layers graphene) study verifies the strong hot electron scattering correlations, exhibiting intriguing two-dimensional properties into their bulk counterparts. Consequently, the spectral coverage of hot electrons promoted from mid-infrared (4 μm) to near-infrared (1.2–1.6 μm) energy level is achieved, leading to a 10 9  eV −1  cm −2 populated hot electron density for the mid-infrared photodetection. In addition, the consistently increased number of photo-excited electrons via stacking of graphene layers, results in a gradual evolution of subsequent electron thermalization. The proposed scheme for exploring the thickness dependence electron thermalization property of the graphitic material paves the way to design ultrafast and sensitive mid-infrared photodetecters. Graphical abstract: Image 1